Cellulases from penicillium janthinellum mutants: solid-state production and their stability in ionic liquids - Adsul, Mukund G.; Terwadkar, Asawari P.; Varma, Anjanikumar; Gokhale, Digambar V. (Bioresources, 2009)
The cellulase production by P. janthinellum mutants on lignocellulosic material such as cellulose or steam exploded bagasse (SEB) in combination with wheat bran was studied in solid state fermentation (SSF). One of the mutants, EU2D21, produced the highest levels of endoglucanase (3710 IU g(-1) carbon source) and beta-glucosidase (155 IU g(-1) carbon source). Ionic liquids are so-called green solvents that have become attractive for biocatalysis. Stability of mutant cellulases was tested in 10-50% of the ionic liquid 1-butyl-3-methylimidazolium chloride ([bmim]Cl). FPA and CMCase were significantly stable in 10% ionic liquid after 5h. beta-glucosidase showed 85% of its original activity after 5 h incubation in 30% ionic liquid and retained 55% of its activity after 24 h. This enzyme preparation hydrolyzed ionic-liquid-treated SEB completely in 15 h in the presence of 20% ionic liquid. These studies revealed that there is no need of regenerating cellulose after ionic liquid treatment, since cellulase of mutant strain was found to be significantly stable in the ionic liquid.
Keywords: Cellulase stability; Ionic liquid; Mutant cellulase; Solid state fermentation